Development of norepinephrine transporter reuptake inhibition assays using SK-N-BE(2)C cells. Issue 5 (May 2018) - Decker, Ann M.; Blough, Bruce E.
Abstract: This report describes efforts to develop and validate novel norepinephrine transporter reuptake inhibition assays using human neuroblastoma SK-N-BE(2)C cells in 24-well format. Before conducting the assays, the SK-N-BE(2)C cells were first evaluated for their ability to uptake [ 3 H]norepinephrine and were shown to have a saturable uptake with a KM value of 416 nM. Using this determined KM value, reuptake inhibition assays were then conducted with a variety of ligands including antidepressants, as well as piperazine and phenyltropane derivatives. The results obtained with the SK-N-BE(2)C cells indicate that this model system can detect a range of ligand potencies, which compare well with other established transporter assays. Our data suggest that SK-N-BE(2)C cells have potential utility to serve as another model system to detect norepinephrine reuptake inhibition activity.